Nutritional status in perianal Crohn’s disease: are we underestimating the impact? - Alves Martins, Bruno Augusto; Filho, Oswaldo de Moraes; Lopes, Ana Carolina Benvindo; de Faria, Ricardo Jacarandá; Silva, Clíslian; Lemos, Gabriela de Oliveira; Silveira, Dannilo Brito; de Sousa, João Batista (Frontiers in Nutrition, 2023)
Symptomatic perianal disease is common in patients with Crohn’s disease (CD), and perianal fistulas represent the primary form of anal involvement. This type of involvement is associated with a poor prognosis and a disabling course. The treatment is challenging and involves both surgical and medical approaches. Despite combined therapy, a significant portion of patients may still require proctectomy to control the symptoms. Consequently, investigating factors that may influence the outcome of perianal disease remains a priority area of research in CD. Nutritional deficiencies are well documented among CD patients with luminal forms of involvement and are closely related to poor clinical outcomes, therapy response, and postoperative complications. As a result, leading guidelines recommend regular nutritional assessment and correction of nutritional deficiencies in patients requiring a surgical approach. Despite these recommendations and the high rate of surgeries among CD patients with perianal disease, there is a shortage of studies addressing the real impact of nutritional status on the course and outcomes of perianal disease. This knowledge gap underscores the importance of further research to understand better and improve the management of perianal CD. This narrative review aims to provide an overview of nutritional status assessment and the influence of nutritional status on the outcomes of patients with perianal CD.